Implementasi Kebijakan Beasiswa Afirmasi dalam Meningkatkan Akses Pendidikan Tinggi bagi Orang Asli Papua - Aryoko A F Rumaropen; Akbar Silo; Vince Tebay; Yustus Pondayar; Yesaya Sambra Saneraro Wamaer (JURNAL EKOLOGI BIROKRASI, 2025)
This study examines the implementation of the affirmative scholarship policy in Papua Province and its contribution to the development of human resources among Indigenous Papuans (Orang Asli Papua/OAP). The policy was introduced as part of the government’s effort to reduce educational inequality and expand access to higher education for communities that have historically experienced structural disadvantages. Despite its strategic objectives, the implementation of the scholarship program has encountered several governance and administrative challenges. This research employs a qualitative descriptive approach to explore the dynamics of policy implementation. Data were collected through in-depth interviews, focus group discussions, and document analysis involving government officials, scholarship administrators, higher education institutions, and scholarship recipients. Informants were selected using purposive and snowball sampling techniques. Data were analyzed using an interactive qualitative model consisting of data reduction, data display, and conclusion drawing, complemented by a SWOT analysis to identify strengths, weaknesses, opportunities, and threats in policy implementation. The findings show that the affirmative scholarship policy has expanded access to higher education for Indigenous Papuans and contributed to strengthening regional human resource capacity. However, its effectiveness is influenced by institutional capacity, administrative governance, coordination among implementing agencies, and the availability of reliable data systems. Challenges such as delays in scholarship fund disbursement and weak monitoring mechanisms remain significant issues. Strengthening governance structures, improving institutional coordination, and developing integrated information systems are therefore essential to enhance the sustainability and effectiveness of the affirmative scholarship policy in supporting equitable human resource development in Papua.